Evaluation of Cytotoxicity and Genotoxicity of Inula viscosa Leaf Extracts with Allium Test. (23rd June 2010) - Aşkin Çelik, Tülay; Aslantürk, Özlem Sultan
Abstract : I. viscosa has been used for years in folk medicine for its anti-inflammatory, antipyretic, antiseptic, and paper antiphlogistic activities. In this study, cytotoxic and genotoxic effects of I. viscosa leaf extracts on the root meristem cells of Allium cepa have been examined. Onion bulbs were exposed to 2.5 mg/ml, 5 mg/ml, and 10 mg/ml concentrations of the extracts for macroscopic and microscopic analysis. Tap water has been used as a negative control and Ethyl methanesulfonate (EMS) (2 ⋅ 10 − 2 M) has been used as a positive control. The test concentrations have been determined according to doses which are recommended for use in alternative medicine. There has been statistically significant (P < .05 ) inhibition of root growth depending on concentration by the extracts when compared with the control groups. All the tested extracts have been observed to have cytotoxic effects on cell division in A. cepa. I. viscosa leaf extract induces the total number of chromosomal aberrations and micronuclei (MNC) formations in A. cepa root tip cells significantly when compared with control groups. Also, this paper shows for the first time the induction of cell death, ghost cells, cells with membrane damage, and binucleated cells by extract treatment. These results suggest the cytotoxic and genotoxic effects of the I. viscosa leaf extracts on A. cepa .